131 Meta-analysis of Primary Care Interventions to Address Frailty Among Adults Aged 65+. (16th September 2019) - Macdonald, Steve; Travers, John; Shé, Éidín Ní; Bailey, Jade; Romero-Ortuno, Roman; Keyes, Michael; O'Shea, Diarmuid; Cooney, Marie Therese
Abstract: Background: Frailty can contribute to poor clinical outcomes including disability, illness, and death. Intervention against frailty may help older adults maintain overall health and independence, and a growing body of recent literature describes interventions specifically targeting frailty. The diversity of measurement constructs and intervention types raises a challenge for those seeking to identify best-practice strategies to manage frailty in the primary care setting, therefore this study aimed to quantify the relative effectiveness of reported interventions. Methods: PubMed, CINAHL, Cochrane Register of Controlled Trials, and PEDr databases were interrogated, and reference lists of retrieved studies were also examined. For comparisons, articles were grouped by intervention and meta-analysis using the random effects model was performed wherever two or more studies examined the same outcome measure using similar interventions. Results: 29 studies with a total of 4430 participants were included in this series of meta-analyses. Interventions included exercise (alone or plus nutrition supplementation or education), nutrition supplementation alone, comprehensive geriatric assessment (CGA), and hormone supplementation. Outcome measures included frailty (Fried criteria), physical performance, leg strength, and grip strength, among others. Interventions varied in relative effectiveness. When comparing studies that assessed frailty status using Fried's criteria, exercise alone (n=3, RR=0.63 (CI 0.47–0.85), I 2 =0%) appeared effective versus control in improving status, as did exercise plus nutritional supplementation (n=2, RR=0.62 (CI 0.48–0.79), I 2 =0%), and exercise plus nutritional education (n=3, RR=0.69 (CI 0.58–0.82), I 2 =0%). CGA also appeared effective in improving frailty status (n=3, RR=0.77 (CI 0.64–0.93), I 2 =0%). Conclusion: This series of meta-analyses indicates that several intervention types are associated with positive improvements in frailty status, and frailty-associated indicators. These results agree with previous findings, and represent an up-to-date quantitative synthesis of available literature on primary care interventions addressing frailty among older adults.